Controlled trial of enalapril in congestive cardiac failure. Issue 4 (October 1985) - McGrath, B P; Arnolda, L; Matthews, P G; Jackson, B; Jennings, G; Kiat, H; Johnston, C I
Abstract : Twenty five patients with chronic congestive cardiac failure had enalapril (n = 13) or placebo (n = 12) added to their existing regimen of digoxin and frusemide in a randomised double blind trial. Four hours after the first 5 mg dose, the enalapril group showed significant falls in blood pressure, heart rate, and concentrations of plasma angiotensin II, angiotensin converting enzyme, and noradrenaline. During the 12 week trial heart failure became worse in one enalapril treated patient (8%) and in seven placebo treated patients (58%). There were no significant changes in cardiac ejection fraction or exercise duration in either group. Plasma noradrenaline response to graded exercise and maximum exercise rate-pressure product were significantly reduced after four and 12 weeks of active treatment but unchanged with placebo treatment. There was a sustained increase in plasma potassium and a slight rise in plasma creatinine in the enalapril group. Plasma concentrations of the active drug, enalaprilate, were dose related and log enalaprilate correlated significantly with percentage of plasma angiotensin converting enzyme activity (r = -0.66). Enalapril was well tolerated and produced no adverse effects. The drug appears to be superior to placebo and offers considerable promise for the treatment of this condition.